Quality of water resources in the Niger basin and in the region of Lagos (Nigeria) - Adeaga, Olusegun; Mahe, Gil; Dieulin, Claudine; Elbaz-Poulichet, Francoise; Rouche, Nathalie; Seidel, Jean-Luc; Servat, Eric (Bulletin of Geography. Physical Geography Series, 2017)
Water quality studies in Nigeria are usually conducted at local scales and limited to a restricted number of chemical contaminants while reliable data on trace metals (including arsenic) concentrations are relatively scarce. This study focuses on available renewable water resources quality of selected sampled locations for major ions and trace elements concentration in the Lower River Niger basin and part of Lagos region. A screening of water contamination by arsenic and heavy metal was carried out through water sampling collection at selected locations using in-situ measurement and Laboratory testing to estimate heavy metal concentrations and water type. The analysis reveals moderate Trace element contamination of the water resource with the exception of Pb while Mn and to a lesser extend Al exceeded WHO quality standards, but the Arsenic concentrations are lower than the drinking water quality standards and are safe for consumption and irrigation while the water type is Bicarbonate.